2013
DOI: 10.1007/978-3-642-34216-5_31
|View full text |Cite
|
Sign up to set email alerts
|

Effect Sulfur and ZnO Nanoparticles on Stress Physiology and Plant (Vigna radiata) Nutrition

Abstract: Phytotoxic and agro beneficial properties of antimicrobially efficient Sulfur nanoparticles (SNPs) and ZnO nanoparticles (ZNPs) were evaluated on Mung (Vigna radiata). Mung seeds were germinated with an increasing concentration gradient of nanoparticles. The extent of phtotoxicity were assessed depending upon the effect of used nanoparticles on physical factors (relative root and shoot length, dry weight and area of leaves), photosynthetic pigments (chlorophyll, carotene and xanthophyll content) and mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 10 publications
3
18
0
Order By: Relevance
“…ZnO NPs did not affect germination rates at 250 and 500 mg/kg (Figs. 1 and S3 SM), which followed the previously reported data on mung beans (Patra et al, 2013). However, the germination rate increased to 23% at 750 mg/kg ZnO NP treatment, compared to control.…”
Section: Effect On Seed Germinationsupporting
confidence: 86%
See 2 more Smart Citations
“…ZnO NPs did not affect germination rates at 250 and 500 mg/kg (Figs. 1 and S3 SM), which followed the previously reported data on mung beans (Patra et al, 2013). However, the germination rate increased to 23% at 750 mg/kg ZnO NP treatment, compared to control.…”
Section: Effect On Seed Germinationsupporting
confidence: 86%
“…However, the leaf area index was in order: bulk ZnO N ionic Zn N ZnO NPs. This suggests that at 500 mg/kg, the bulk form/species impacted the meristematic tissue; increasing cell division, resulting in increased leaf area (Patra et al, 2013). We also observed that the bulk treatments triggered the early flowering of alfalfa in 2 months, which suggests that at 500 mg/kg, bulk ZnO acted as growth enhancer for this particular alfalfa genotype (Skoog, 1940).…”
Section: Changes In Leaf Areamentioning
confidence: 65%
See 1 more Smart Citation
“…Utilization of nanotechnological tools (Gopal et al 2012a) for the development of crop protection products has received much attention (Choudhury et al 2010;Patra et al 2013). Nanopesticides, an emerging technological development, have increased bioefficacy, lower application dose and less harmful to the environment than conventional formulations (Gopal et al 2011a(Gopal et al , b, 2012bKumar et al 2011Kumar et al , 2012.…”
Section: Introductionmentioning
confidence: 95%
“…Nanotechnology has tremendous potential in food and agriculture (Gopal et al 2012a). A need was felt for testing new age formulation of pesticides such as nanosized formulations (Choudhury et al 2010;Patra et al 2013) which have been proved to be more effective than conventional formulations and have better insecticidal activity (Hwang et al 2011).…”
Section: Introductionmentioning
confidence: 99%